A Study on corporate board model - Cho, Chung-Myong (KDI School, 1998)
Corporate governance is an Important topic in today''s global business and a key element of Korean economic reform packages since the IMF crisis The board of directors IS an essential system in maintaining m the balance between shareholders and managers and Its effectiveness is critical for the competitiveness of a firm m today''s era of global competition Today, there is a tendency to adapt the Anglo-Saxon model as a global standard Characteristics of the Anglo-Saxon board model are the majority outside board, various committees, active role of the board, and well-established norms of behavior In contrast, the all-executive board, power concentration at the top, and weak role of the board, characterized corporate boards in Korea before the IMF crisis. In that sense, it IS time that the boards in Korea make changes m order to revive and survive under a globally competitive environment Today, Korean companies face the breakdown of the old economic system and face fundamentally changing financial environment. Accordingly, the reform of the board is not a question of choice but one of necessity The reform programs Initiated by the Korean government mainly focus on the introduction of outside directors to enhance transparency and accountability of corporate management through "checks and balances " The reform direction is in line with the Anglo-Saxon model and OECD principles Meanwhile, POSCO, one of the most successful Korean corporation since the 1960s, now faces fundamental changes as a result of Its anticipated privatization In order to respond to new challenges such as the increase of foreign investors and institutional investors, POSCO should reform Its board m terms of role, operating practices, board composition, and committees
Thesis(Master) --KDI School:Master of Business Administration,1998